Comparative and combined effects of transforming growth factors alpha and beta, interleukin-1 and interferon-gamma on rheumatoid synovial cell proliferation, glycolysis and prostaglandin E production. - Taylor, D; Feldmann, M; Evanson, J; Woolley, D (Springer-Verlag, 1989)
Enhanced cell proliferation, glycolysis and prostaglandin E production are all characteristic features of rheumatoid synovial tissue. The interrelationships of these three cellular parameters have been examined using rheumatoid synovial fibroblasts and their responses to specific cytokines in vitro. Transforming growth factor alpha (TGF alpha) caused a more than threefold increase in synovial cell proliferation whilst transforming growth factor beta (TGF beta), interleukin-1 alpha (IL-1 alpha) and interferon-gamma (IFN-gamma) produced only marginal changes. The combined addition of IL-1 alpha with TGF beta resulted in an enhanced proliferative response comparable with that produced by TGF alpha. Glycolysis, estimated by glucose utilisation and measurements of the glycolytic regulatory metabolite fructose 2,6-bisphosphate was significantly stimulated by TGF beta, IL-1 alpha and IFN-gamma, but less so by TGF alpha. Prostaglandin E production was significantly increased by IL-1 alpha to an extent much greater than that produced by TGF alpha or TGF beta, although the combined addition of IL-1 alpha with either TGF alpha or beta resulted in a synergistic increase in PGE production, a response partly diminished by the addition of IFN-gamma. These findings suggest that the extent to which a cytokine stimulates glycolysis is not consistently related to its mitogenicity, and that cytokine combinations which stimulate high levels of PGE production (a growth inhibitor) will not necessarily be associated with a reduced rate of cellular proliferation in cultured, adherent, rheumatoid synovial fibroblasts.